EFFECTS OF COMBINING THE O2O MODEL, REGIONAL PRODUCTS AND EDUCATIONAL EXPERIENCE ON THE DEVELOPMENT OF VIETNAM’S RURAL E-COMMERCE - Tran Nho Quyet,; Guang Ji Tong,; Nguyen Thi Thanh Hien, (Journal of Forestry Science and Technology, 2022)
Rural E-commerce has performed as a new area to consider, primarily takes spontaneous nature and it does not have an obvious orientation. As a result, rural E-commerce needs to select a suitable development model to form the breakthrough premise for Vietnam’s agriculture. Moreover, the core goal of this model is to intensify agricultural trading to build a modern agricultural product trading system (1 out of 3 new TAM NONG ideological criteria). Along with the purpose to exploit the potential in rural areas, increase the farmers’ income and improve the standard of living - a foundation to create a green, clean and beautiful environment, modernize the agricultural economy; the research is also of great significance in the development of modern TAM NONG policy with recent 4.0 technology in Vietnam. This research uses a cross-sectional descriptive method, aiming at shedding light on the key factor for the development of rural E-commerce in Vietnam based on the O2O model, including the ability to participate in E-commerce (age, gender, etc), living areas (rural, urban), academic level, combining of cultural, rural, regional specialties in developing field-trip ecotourism, managing logistics. As a result, our research aims to establish a new rural E-commerce combining 3 in 1: E-commerce O2O model, rural specialties, together with rural educational experience.